Answer:
Part 1) The directrix of the parabola is y=-4.25
Part 2) The focus of the parabola is F(1,-3.75)
Step-by-step explanation:
we have
[tex]y=x^{2}-2x-3[/tex]
This is a vertical parabola open upward
we know that
If a parabola has a vertical axis, the standard form of the equation of the parabola is
[tex](x - h)^{2}=4p(y - k)[/tex]
where
pā 0
The vertex of this parabola is at (h, k).
The focus is at (h, k + p).
The directrix is the line y = k - p.
The axis is the line x = h.
step 1
Convert the equation of the parabola in standard form
[tex]y=x^{2}-2x-3[/tex]
[tex]y+3=x^{2}-2x[/tex]
[tex]y+3+1=x^{2}-2x+1[/tex]
[tex]y+4=x^{2}-2x+1[/tex]
[tex]y+4=(x-1)^{2}[/tex]
so
[tex](x-1)^{2}=(y+4)[/tex] ----> equation in standard form
The vertex is the point (1,-4)
4p=1 ------> p=1/4
step 2
Find the directrix of the parabola
The directrix is the line y = k - p
we have
k=-4
p=1/4
substitute the values
y = k - p
y=-4-(1/4)=-17/4
y=-4.25
step 3
Find the focus of the parabola
we know that
The focus is at (h, k + p).
we have
h=1
k=-4
p=1/4
substitute
F(1,-4+1/4)
F(1,-3.75)